Analysis of the main consensus protocols of blockchain - Zhang, Shijie; Lee, Jong-Hyouk (ICT express, 2020)
Blockchain is the core technology of many cryptocurrencies. Blockchain as a distributed ledger technology has received extensive research attention. In addition to cryptography and P2P (peer-to-peer) technology, consensus protocols are also a fundamental part of the blockchain technology. A good consensus protocol can guarantee the fault tolerance and security of the blockchain systems. The consensus protocols currently used in most blockchain systems can be broadly divided into two categories: the probabilistic-finality consensus protocols and the absolute-finality consensus protocols. This paper introduces some of the main consensus protocols of these two categories, and analyzes their strengths and weaknesses as well as the applicable blockchain types.